A Bitter Pill to Swallow: Portugal’s Lessons For Drug Law Reform in New Zealand - McCaffrey, Hugh (Victoria University of Wellington Law Review, 2009)
On 1 July 2001, Portugal decriminalised all drugs, replacing criminal sanctions with administrative ones. Portugal’s decriminalisation policy focused on individual possession and use of drugs. It was thought that possession and use would be best dealt with outside of the criminal process. In New Zealand, the Law Commission is revisiting the Misuse of Drugs Act 1975. The author seeks to analyse the first two terms of reference: whether the legislative regime should reflect the principle of harm minimisation underpinning the National Drug Policy; and the most suitable model or models for the control of drugs. This paper examines the principles around the criminalisation of possession and use of drugs. In particular, it examines the experience of Portugal, some eight years after decriminalisation. It is argued that New Zealand should adopt a policy of harm minimisation and that the model Portugal presents ought to be seriously considered as a possibility for New Zealand reform.